1986
DOI: 10.1073/pnas.83.8.2422
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of lipid bilayer vesicles by sucrose during freezing

Abstract: The freeze-induced fusion and leakage of small unilamellar vesicles (SUV) of natural and synthetic phosphatidylcholines and the suppression of these processes by sucrose was studied by electron microscopy, by high-resolution NMR, and by ESR techniques. During slow freezing of SUV suspensions in water, the lipid was compressed into a small interstitial volume and transformed into a multilamellar aggregate without vesicular structure. When frozen in sucrose solution, the lipid also was compressed between the ice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
90
0
2

Year Published

1988
1988
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(96 citation statements)
references
References 24 publications
4
90
0
2
Order By: Relevance
“…We show specifically that CBF3 overexpression in Arabidopsis results in the accumulation of COR polypeptides, the accumulation of Pro, and the accumulation of soluble sugars including Suc, raffinose, Glc, and Fru. There is evidence to indicate that each of these "classes" of biochemical alterations-COR polypeptides (Thomashow, 1998), Pro (Rudolph and Crowe, 1985;Carpenter and Crowe, 1988;Nanjo et al, 1999), and sugars (Strauss and Hauser, 1986;Carpenter and Crowe, 1988;Koster and Lynch, 1992;Wanner and Junttila, 1999)-contribute to an enhancement of freezing tolerance. It is interesting that we also found that Arabidopsis plants overexpressing CBF3 displayed a prostrate growth habit, a phenotype that has been associated with cold acclimation, and increased freezing tolerance in other plants (Omran et al, 1968;Roberts, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We show specifically that CBF3 overexpression in Arabidopsis results in the accumulation of COR polypeptides, the accumulation of Pro, and the accumulation of soluble sugars including Suc, raffinose, Glc, and Fru. There is evidence to indicate that each of these "classes" of biochemical alterations-COR polypeptides (Thomashow, 1998), Pro (Rudolph and Crowe, 1985;Carpenter and Crowe, 1988;Nanjo et al, 1999), and sugars (Strauss and Hauser, 1986;Carpenter and Crowe, 1988;Koster and Lynch, 1992;Wanner and Junttila, 1999)-contribute to an enhancement of freezing tolerance. It is interesting that we also found that Arabidopsis plants overexpressing CBF3 displayed a prostrate growth habit, a phenotype that has been associated with cold acclimation, and increased freezing tolerance in other plants (Omran et al, 1968;Roberts, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that Pro can protect both membranes and proteins against freeze-induced damage in vitro (Rudolph and Crowe, 1985;Carpenter and Crowe, 1988) and direct evidence that increased levels of Pro enhances whole plant freezing tolerance (Nanjo et al, 1999). Suc and other simple sugars have also been shown to be effective cryoprotectants in vitro (Strauss and Hauser, 1986;Carpenter and Crowe, 1988) and there is correlative evidence indicating a role in freezing tolerance in coldacclimated plants (Guy et al, 1992;Koster and Lynch, 1992;Wanner and Junttila, 1999). A question thus raised is whether the CBF transcription factors are limited to activating the expression of COR genes encoding cryoprotective polypeptides, or alternatively, have a role in activating multiple components of the cold acclimation response.…”
mentioning
confidence: 99%
“…Exceptions are charged phospholipids which also form some uni-and oligo-lamellar structures and some double-chained surfactants which form spontaneously stable vesicles (Talmon et al, 1983 (Crowe et al, 1985). This phenomenon is probably due to the specific interaction of sugars with polar heads and can be very useful for the long-term storage of vesicles (Strauss & Hauser, 1986;Crowe et al, 1987).…”
Section: Preparation Methodsmentioning
confidence: 99%
“…Proline may protect protein structures by maintaining their structural stability (Bates et al 1973), and, accordingly, drought stress significantly increases proline accumulation (Sofo et al 2004, Ren et al 2006. Soluble sugars acting as osmoprotectors stabilize proteins and membranes, most likely substituting the water in the formation of hydrogen bonds with polypeptide polar residues (Crowe et al 1992) and phospholipid phosphate groups (Strauss and Hauser 1986). An increase in the soluble protein concentration under drought stress could be related to an increase in the protein synthesis related to acclimation and reprogramming to new conditions as well as to cell protection against these stresses (Chen and Plant 1999).…”
Section: Discussionmentioning
confidence: 99%